Investigating sound: Visual and aural style from Broadchurch to Gracepoint. Issue 1 (1st April 2017) - Keeler, Amanda
Using Broadchurch and its American version Gracepoint as a case study, this article explores the aesthetic relationship between these two television programmes through an analysis of their visual and aural styles. The increasing proliferation of television-to-television adaptations and remakes necessitates revisiting the terminology to assess how it accommodates methodological approaches that extend beyond cross-cultural analyses. As narrative content and style are inextricably connected, this article attends to the complexity of employing existing terms to analyse the new version of a programme that simultaneously replicates and departs from the style and tone of its predecessor.